2015
DOI: 10.24200/jams.vol20iss0pp24-29
|View full text |Cite
|
Sign up to set email alerts
|

Biofouling on artificial substrata in Muscat waters

Abstract: Macro-fouling communities developed on acrylic, aluminum, wood and fiberglass panels were investigated after 4 months exposure in Marina Bandar al Rawdah and Marina Shangri La. Wet weight of biofouling was about 2-fold higher in Marina Bandar Rawdah and different communities were formed on the front and back sides of the panels. Differences between communities on different materials were less pronounced. In the second study, wet weight and community composition of macro-fouling communities on ceramic tiles at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
2
7
0
1
Order By: Relevance
“…Barnacles were one of the primary drivers of the divergence of Sea of Oman reefs from the other regions, with barnacles here covering nearly a quarter of settlement tiles (22%) on average, compared with low abundance in the Musandam (5% cover) and a near absence in the Gulf (0.2% cover). Barnacles are reported to be among the most abundant members of settlement communities in Oman (Wallström et al, 2011;Dobretsov et al, 2013;Polman et al, 2013;Dobretsov, 2015), likely a reflection of their success as filterfeeders in this high-productivity environment (Sheppard et al, 1992), suggesting that the high barnacle abundance we observed is a result of long-term supply dominance in the Sea of Oman.…”
Section: Discussionsupporting
confidence: 46%
“…Barnacles were one of the primary drivers of the divergence of Sea of Oman reefs from the other regions, with barnacles here covering nearly a quarter of settlement tiles (22%) on average, compared with low abundance in the Musandam (5% cover) and a near absence in the Gulf (0.2% cover). Barnacles are reported to be among the most abundant members of settlement communities in Oman (Wallström et al, 2011;Dobretsov et al, 2013;Polman et al, 2013;Dobretsov, 2015), likely a reflection of their success as filterfeeders in this high-productivity environment (Sheppard et al, 1992), suggesting that the high barnacle abundance we observed is a result of long-term supply dominance in the Sea of Oman.…”
Section: Discussionsupporting
confidence: 46%
“…Distribution: Apart from the Red Sea, its distribution is not well known ( Vine, 1986 ; Ostrovsky et al, 2011 ). However, it has recently been found in the Gulf of Oman ( Dobretsov, 2015 ). Its first and only Mediterranean record (prior to our new records listed below) is from Tripoli, Lebanon ( Harmelin, 2014 ).…”
Section: New Nis Records: Notes On Individual Speciesmentioning
confidence: 99%
“…Previous studies have shown that the amount of free space on the panels usually decreases with the progression of the succession, especially when early colonizers exhibit high growth rates and prevent the settlement of new ones (Benedetti-Cecchi 2000, Cifuentes et al 2010, Lindeyer andGittenberger 2011). The biomass of biofoulers on the LTP, ranged from 722 (after 2 months) to 2559 g·m -2 (after 12 months), being much lower than those observed in the Indian ocean, specifically for the Gulf of Oman (4-months age panel, wet weight: 6000 g·m -2 , Dobretsov et al 2015) and the Bay of Bengal (6-month age panel, wet weight: 6392 g·m -2 , Pati and Rao 2015).…”
Section: Discussionmentioning
confidence: 99%